The Adherence to Healthy Lifestyle Among Arab Patients With Cardiovascular Disease: Mixed-Method Review. (January 2022) - Alomari, Albara; Alananzeh, Ibrahim; Lord, Heidi; Fernandez, Ritin
Introduction: Cardiovascular disease (CVD) accounts for 25% to 45% of deaths among Arab people. The purpose of this review was to investigate the level, predictors, motivators, and barriers to adherence to lifestyle recommendations among Arab patients with CVD. Method: A systematic search of the literature was conducted and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. MEDLINE, EMCARE, CINAHL, Scopus, and the Cochrane Central Register of Controlled Trials were searched. Studies that explored adherence to a healthy lifestyle among Arab adult patients with CVD were included. Results: Twelve studies were included. Quantitative results showed low adherence among Arab people with CVD. Qualitative synthesized results revealed that internal motivators, personal desire as well as structural drivers impact the patient's ability to adhere to a healthy lifestyle. Discussion: Multidimensional solutions that consider religion and culture and include active involvement of families are required to improve adherence.